the Effects of Inspiratory Muscle Training on Hand and Mobility Functions in Subacute Stroke: Effects of Inspiratory Muscle Training on Hand and Mobility Functions in Subacute Stroke - WF, Nisa; MS, Prananta; F, Arisanti (ASEAN Journal of Rehabilitation Medicine, 2019)
ABSTRACT Objectives: To study the effects of inspiratory muscle training (IMT) on peripheral muscle functions in subacute stroke patients. Setting: Clinics of Neurology and Physical Medicine and Rehabilitation at Hasan Sadikin General Hospital, Bandung. Study design: Double blinded clinical trial. Subjects: Consecutive sampling of 32 subacute stroke patients were recruited into the study and 31 completed the study. Methods: Participants were divided into two groups of an intervention (n=15) and a control (n=16). Both groups received a conventional exercise and ambulatory program. The intervention group performed an 8-week home-based IMT program with intensity of 40% of PI-max (maximal inspiratory pressure) whereas the control group performed IMT program with intensity of 10% of PI-max. Primary outcomes indicating peripheral muscle functions were grip strength of the paretic side assessed with a hand grip dynamometer and mobility function assessed with a sit-to-stand test. Secondary outcome was inspiratory muscle strength measured as PI-max. Outcome measurements were done before and after the intervention ended. Results: After 8 weeks the grip strength of the paretic hand and the score of the sit-to-stand test increased significantly in both groups but there were no differences between the two groups. However, the PI-max significantly increased only in the intervention group (p=0.000) and there was significantly different between the two groups (p=0.003). Conclusion: A home-based inspiratory muscle training was effective in increasing inspiratory muscle strength. However, it did not demonstrate any effect on peripheral muscle functions, grip strength and ability of sit-to-stand in subacute stroke patients.